Universell stolkonstruktion : Till Hägglunds fordon - Eriksson, Johan (2011)
When BAE Systems Hägglunds AB today designs a new seat to its vehicles, the seat is individual adapted to fit in that position. The goal of this thesis was instead of personalizing a seat, design a seat that can be used in several positions in several vehicles. The original idea was to design a seat that would work for use in three Hägglund vehicles, Armadillo, Bvs10 and CV90. The seat should work as driver's seat in CV90 and Bvs10 as well as chief and commander seat in Armadillo and CV90. Since Hägglunds manufactures vehicles, specializing in the defense industry, the vehicles that the seat is used in today are war affected zones worldwide. This means that the requirements on the seats are very high. To avoid injury from things like IED’s (improvised explosive device), the demanded requirements have risen on seat designs and its attachment so much that the seat must not be significantly affected from the explosions. By planning the thesis in order to maintain a high quality, the thesis followed in most part a product development process developed at Luleå University called Sirius Masterplan (Appendix 3). The report describes the work from planning stage to the finished solution. Where the finished result has been produced in form of a delivered CAD-model of the seat concept, designed in Catia V5R20. The conclusion shows that seat concept with a few modifications on some positions, will serve for use in all positions. However, there are both positive and negative attributes of the concept. A negative feature is that the seat's weight is greatly affected by the need to cope with a person at a standing position within the tower location in the CV90, which in turn affects the look and weight of the remaining positions. A positive feature is that the seat will operate in all positions, within the boundaries, a fact that should reduce the costs of manufacturing. Validerat; 20110830 (anonymous)